A clinical study of trans-rectus sheath extrapreperitoneal procedure and Gilbert’s repair in the treatment of groin hernia - Shafiq, Nida; Jeelani, Shaukat; Mushtaq, Umer; Mir, Tauqeer A. (International Surgery Journal, 2022)
Background: The focus to improve surgical technique has changed from recurrence to chronic postoperative inguinal pain (CPIP). Nerve injury or stretching due to surgical approach or mesh fixation led to CPIP. Transrectus sheath preperitoneal procedure (TREPP) is a new open technique in which the mesh is placed preperitoneally via medial approach. The goal of this study was to evaluate and compare the results of TREPP with another open anterior approach- Gilbert’s repair which also doesn’t need mesh fixation; in view of operative time, duration of hospital stay, CPIP, recurrence and cost effectiveness. Methods: Between November 2013 and October 2015, an observational clinical study of TREPP and Gilbert’s repair in the treatment of groin hernia was conducted in the department of surgery, SMHS Hospital. Patients were enrolled after detailed history, clinical examination, all baseline investigations. Results: A total of 40 patients above 18 years of age with primary unilateral inguinal hernia were operated: 20 with TREPP and remaining 20 with Gilbert’s technique. Out of those who underwent TREPP 75% had indirect type and 25% had direct type hernia. Similarly, out of those who underwent Gilbert’s repair, 65% had indirect type and 35% had direct hernia. Operative time was significantly lower in TREPP with mean of 58.6±11.47 minutes in comparison to 68.4±9.54 minutes in Gilbert’s repair. Also, the mean hospital stay was 21.2±3.69 hours in TREPP whereas it was 31.2±6.03 hours in Gilbert’s repair. Conclusions: TREPP is a more feasible new technique for inguinal hernia repair with better results in terms of CPIP especially. It is more promising because of the complete preperitoneal view, the short learning curve, and the stay-away-from-the-nerves principle thereby offering better outcome and patient satisfaction.